Structural analysis of polymeric composite materials - Tuttle, M. E. (Boca Raton : CRC Press/Taylor & Francis Group, 2013)
'Emphasizing the macromechanical (structural) level, over micromechanical issues and analyses, this unique text covers crucially important effects of environment, that is, effects due to temperature changes or moisture content, at the outset to establish a coherent and updated knowledge base. Each chapter includes numerical example problems to illustrate the concepts presented. Updated with new examples, problems, and improved flow, this second edition includes a solutions manual for qualifying course adoptions and a suite of computer programs that implement the analyses discussed. Emphasizes the macromechanical (structural) level over micromechanical issues and analyses. Discusses crucially important effects of environment in order of relevance (i.e., effects due to temperature changes and/or moisture content are incorporated into early chapters instead of treated separately in later chapters). Includes numerical example problems in each chapter that illustrate the concepts presented. Offers a solutions manual for qualifying adoptions. Offers access to a suite of computer programs available on the author's website that implement the analyses discussed in the text'--
Includes bibliographical references and index.
Keywords: Polymeric composites; Structural analysis (Engineering).